2000
DOI: 10.1109/82.850420
|View full text |Cite
|
Sign up to set email alerts
|

Bandpass ΣΔ modulator employing undersampling of RF signals for wireless communication

Abstract: The rapid development of digital wireless systems has led to a need for high-resolution and high-speed bandpass analog-to-digital converters. Continuous-time bandpass 61 modulators are very suitable for such high frequency applications. In this paper, analysis and simulation of a continuous-time bandpass 61 modulator for use in modern cellular/PCS receivers is given. The design employs undersampling relative to a radio receiver's radio frequency (RF) or intermediate frequency (IF) center frequency, while overs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(23 citation statements)
references
References 14 publications
0
23
0
Order By: Relevance
“…The delays between the coefficients are chosen to be a half sampling period in order to give more flexibility for the design method. The choice of the DAC transfer function is critical for undersampled modulators in order to preserve the feedback signal [10]. It has been shown that return-to-zero (RZ) [5] and raised-cosine [2] signals could be used in undersampled architectures.…”
Section: Design Of the Noise Transfer Functionmentioning
confidence: 99%
“…The delays between the coefficients are chosen to be a half sampling period in order to give more flexibility for the design method. The choice of the DAC transfer function is critical for undersampled modulators in order to preserve the feedback signal [10]. It has been shown that return-to-zero (RZ) [5] and raised-cosine [2] signals could be used in undersampled architectures.…”
Section: Design Of the Noise Transfer Functionmentioning
confidence: 99%
“…Crest factor reduction is applied to the generated signal. We assume that undersampling is used in the feedback branch, limiting the useful bandwidth of the forward branch to 38.4 MHz, as in [13]. In our system model, the target gain g for the predistorted amplifier is 13 dB.…”
Section: Simplified System Modelmentioning
confidence: 99%
“…In order to overcome this limitation, undersampling techniques have been used, e.g. in RF digital receivers including ADC architectures based on bandpass sigma delta modulators working in under-Nyquist conditions [5][6][7]. These structures allow working in the IF band, thus reducing the number of stages, obtaining a wide spurious-free dynamic range, allowing a high level of integration, reducing power consumption, etc.…”
Section: Introductionmentioning
confidence: 99%